Nitric oxide decreases intestinal haemorrhagic lesions in rat anaphylaxis independently of mast cell activation - Tavares, J. Carvalho (Hindawi Publishing Corporation, 1997)
The purpose of this study is to assess the role of nitric oxide (NO) in the intestinal lesions of passive anaphylaxis, since this experimental model resembles necrotizing enterocolitis. Sprague-Dawley rats were sensitized with IgE anti-dinitrophenol monoclonal antibody. Extravasation of protein-rich plasma and haemorrhagia were measured in the small intestine. Plasma histamine was measured to assess mast cell activation. The effect of exogenous NO on the lesions was assessed by using two structurally unrelated NO-donors: sodium nitroprusside and S-nitroso-Nacetyl-penicillamine (SNAP). An increased basal production of NO was observed in cells taken after anaphylaxis, associated with a reduced response to platelet-activating factor, interleukin 1beta, and IgE/DNP-bovine serum albumin complexes. The response to bacterial lipopolysaccharide and dibutyryl cyclic adenosine monophosphate (AMP) was enhanced 24 h after challenge, but at earlier times was not significantly different from that observed in controls. Treatment with either sodium nitroprusside or SNAP produced a significant reduction of the haemorrhagic lesions, which are a hallmark of rat anaphylaxis. The extravasation of protein-rich plasma was not influenced by NO-donors. The increase of plasma histamine elicited by the anaphylactic challenge was not influenced by SNAP treatment. NO-donors protect intestinal haemorrhagic lesions of rat anaphylaxis by a mechanism apparently independent of mast cell histamine release.